Association of cystic fibrosis genetic modifiers with congenital bilateral absence of the vas deferens - Havasi, Viktoria; Rowe, Steven M.; Kolettis, Peter N.; Dayangac, Didem; Sahin, Ahmet; Grangeia, Ana; Carvalho, Filipa; Barros, Alberto; Sousa, Mario; Bassas, Lluis; Casals, Teresa; Sorscher, Eric J. (ELSEVIER SCIENCE INC, 2010)
Objective: To investigate whether genetic modifiers of cystic fibrosis (CF) lung disease also predispose to congenital bilateral absence of the vas deferens (CBAVD) in association with cystic fibrosis transmembrane conductance regulator (CFTR) mutations. We tested the hypothesis that polymorphisms of transforming growth factor (TGF)-beta 1 (rs 1982073, rs 1800471) and endothelin receptor type A (EDNRA) (rs 5335, rs 1801708) are associated with the CBAVD phenotype. Design: Genotyping of subjects with clinical CBAVD. Setting: Outpatient and hospital-based clinical evaluation. Patient(s): DNA samples from 80 subjects with CBAVD and 51 healthy male controls from various regions of Europe. This is one of the largest genetic studies of this disease to date. Intervention(s): None. Main Outcome Measure(s): Genotype analysis. Result(s): For single nucleotide polymorphism (SNP) rs 5335, we found increased frequency of the CC genotype among subjects with CBAVD. The difference was significant among Turkish patients versus controls (45.2\% vs. 19.4\%), and between all cases versus controls (36\% vs. 15.7\%). No associations between CBAVD penetrance and polymorphisms rs 1982073, rs 1800471, or rs 1801708 were observed. Conclusion(s): Our findings indicate that endothelin receptor type A polymorphism rs 5335 may be associated with CBAVD penetrance. To our knowledge, this is the first study to investigate genetic modifiers relevant to CBAVD. (Fertil Steril (R) 2010

94: 2122-7. (C) 2010 by American Society for Reproductive Medicine.)
Keywords: Congenital bilateral absence of the vas deferens; CBAVD; CFTR; cystic fibrosis; CF; modifier gene; TGF-beta; EDNRA